Mechanical Behavior and Crack Resistance of Modified Polydimethylsiloxane Impermeable Coating for Concrete Lining Subjected to Ultra-High Internal Pressure - Yong Xia; Jiaqi Wu; Xingyi Yang; Long Qu; Hongqiang Xie (Applied Sciences)
The high water head of some pumped storage power stations will induce the cracking of the concrete lining of their diversion tunnel and the leakage of high-pressure water, which will affect the safety of the tunnel and the surrounding rock. At present, there is no solution to the problem of impermeability of concrete materials after cracking. This paper proposes a composite lining to solve this problem. The composite lining with modified polydimethylsiloxane coating can effectively prevent high-pressure water, but its crack resistance needs to be further studied. Therefore, the tensile mechanical properties, constitutive relationship of modified polydimethylsiloxane impermeable coating, and the crack resistance mechanical properties of modified polydimethylsiloxane impermeable composite lining were studied by laboratory tests and numerical simulations. The results show that the true fracture elongation of the modified polydimethylsiloxane impermeable coating is as high as 118.98%, and its mechanical behavior can be described by a simplified polynomial hyperelastic constitutive model. The in situ stress will affect the crack width of the concrete lining. When the lateral pressure coefficient is less than 1, the crack width decreases with the increase in the lateral pressure coefficient. When the lateral pressure coefficient is greater than 1, the crack width increases with the increase in the lateral pressure coefficient. To prevent the cracking of modified polydimethylsiloxane coating, its spraying thickness needs to increase with the increase in crack width. The ratio of the coating’s thickness to crack width is recommended from 0.162 to 1.930 for internal water pressure from 1 MPa to 10 MPa, respectively. The suggestion provides a reference for designing the impermeable composite lining structure subjected to high internal water pressure.